IMPROVING ACCOUNTING AND REPORTING IN THE DIGITAL ECONOMY - Savkiv, U.S.; Kuzmin, T.L. (The actual problems of regional economy development, 2023)
The article is aimed at studying the influence of the latest digital technologies on the transformation of accounting methodology and practice; application of modern information technologies for collection and processing of accounting information; introduction of new directions for improvement of theoretical, methodical and applied aspects of accounting development. The purpose of the article is to investigate the impact of digital technologies on the transformation of the introduction of accounting in Ukraine, to identify the main opportunities and risks of its implementation. To achieve the goal, the following research methods are used in the article: deduction – to study the advantages and disadvantages of using the latest digital technologies in the practice of accounting; system analysis – to study accounting processes in their relationship and interdependence; synthesis and comprehensive approach – for the study of modern information technologies for collecting, processing and saving accounting information; abstraction - to form generalized conclusions. The article considers a comprehensive approach to the description, storage and processing of data in the accounting system in an automated way; the impact of digital technologies on accounting objects; the procedure for the phased introduction of the computerized regulatory accounting system at the enterprise; peculiarities of using blockchain technology, digital audit, technology «smart» contracts, «cloud» technologies in the practice of accounting The scientific novelty of the study is the identification of key directions for improving the theory and practice of accounting as a result of the introduction of modern digital technologies. The results of scientific research can be applied by enterprises to analyze the state of the current system of the accounting process and to form an effective digital architecture with the aim of its compliance with modern information technologies to improve business processes.